Farmacocinética do Benznidazol administrado em coelhos na forma de comprimidos de liberação imediata e comprimidos de liberação prolongada - Davanço, Marcelo Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Benznidazole (BNZ) is the first-line drug for the treatment of Chagas disease. In Brazil, the drug is available in the form of immediate-release tablets, 100-mg (adult) and 12.5-mg (pediatric); the drug is administered twice or thrice daily for 60 days. The high frequency of daily administrations and the long period of treatment are factors that significantly contribute to the abandonment of therapy, affecting therapeutic success. In this scenario, researchers from Laboratory of Medicine Technology (Federal University of Pernambuco) developed BNZ extended-release tablets (ERK4M and ERK100M). This study aimed to evaluate the preclinical pharmacokinetics of BNZ administered as extended-release tablets (200-mg dose) compared to the tablets currently available. The studies were conducted in rabbits and BNZ quantification was performed in plasma and urine by ultra performance liquid chromatography methods previously validated. The mean residence time (MRT) was twice as high for the tablet ERK100M when compared to the immediaterelease adult. The time to maximum plasma concentration (tmax) was three times higher for the tablet ERK100M when compared to immediate-release adult. The maximum plasma concentration (Cmax) there no was no statistical difference between the different types of tablet (100-mg and 200-mg), demonstrating that even administering a double dose (extended-release tablets), plasma concentrations do not exceed the immediate-release adult tablet (100-mg). The bioavailability of BNZ was adequate in the administration of extended-release tablets and immediaterelease adult tablet; however, with the administration of the pediatric tablet, bioavailability was lower than with other tablets. The pharmacokinetic parameters demonstrated that the ERK100M tablet prolonged drug release from the polymer matrix and provided an increase in the maintenance of the drug concentration in vivo. Thus, a relative bioavailability study in humans will be ...

O benznidazol (BNZ) é o fármaco de primeira escolha para o tratamento da doença de Chagas. No Brasil, este fármaco está disponível na forma de comprimidos de liberação imediata de 100 mg (adulto) e 12,5 mg (pediátrico) e é administrado duas ou três vezes ao dia, durante 60 dias. A alta frequência diária de administrações e o longo período de tratamento são fatores que contribuem significativamente para o abandono da terapia, com consequências sobre o sucesso terapêutico. Diante deste cenário, pesquisadores do Laboratório de Tecnologia de Medicamentos (Universidade Federal de Pernambuco) desenvolveram comprimidos de liberação prolongada de BNZ (LPK4M e LPK100M). Este estudo teve como objetivo avaliar a farmacocinética pré-clínica do BNZ administrado na forma farmacêutica de comprimidos de liberação prolongada (200 mg), comparando-a aos comprimidos atualmente disponíveis. Os estudos foram conduzidos em coelhos e a quantificação de BNZ foi realizada no plasma e urina através de métodos de cromatografia líquida de ultra eficiência previamente validados. O tempo de residência médio (MRT) foi duas vezes maior para o comprimido LPK100M em comparação ao de liberação imediata adulto. O tempo para atingir a concentração plasmática máxima (tmáx) foi três vezes maior para o comprimido LPK100M em relação ao de liberação imediata adulto. Na concentração plasmática máxima (Cmáx) não se observou diferença estatística entre os diferentes tipos de comprimido (100 mg e 200 mg), demonstrando que mesmo administrando o dobro da dose (comprimidos de liberação prolongada), as concentrações plasmáticas não superam as do comprimido de liberação imediata adulto (100 mg). A biodisponibilidade do BNZ foi adequada na administração dos comprimidos de liberação prolongada e no de liberação imediata adulto, no entanto, no pediátrico foi inferior aos demais. Os parâmetros farmacocinéticos mencionados...
Keywords: Química farmacêutica; Chagas, Doença de; Farmacocinética; Medicamentos - Biodisponibilidade; Biodisponibilidade; Bioavailability